Implementation of Village Management Policy based on Digital Transformation Tamansari Village, Licin Sub-District, Banyuwangi Regency, East Java - Bambang Agus Diana; Ridho Harta; Elisa Susanti; Sawitri Budi (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
Digital transformation in villages is becoming an important item on the national policy agenda, driven by efforts to improve public services and empower the rural economy. The purpose of this study is to evaluate the implementation of digital-based village management policies in Tamansari Village, Banyuwangi, highlighting the processes, economic impacts, and governance challenges. This qualitative research method uses in-depth interviews, observation, and document studies of village officials, MSME actors, and BUMDes managers, with source and method triangulation. The results of digitalization implementation strengthen administrative services, expand MSME marketing, and increase transparency in village governance. However, limitations in human resources and digital infrastructure are major constraints. Furthermore, the implication is that optimizing digital training and improving infrastructure become priorities for strengthening the sustainability of digital villages in Indonesia.